2019
DOI: 10.1021/acs.inorgchem.9b02463
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Reaction of Neptunium(V) and Uranium(VI) in Potassium–Sodium Carbonate-Rich Aqueous Media: Speciation Study with a Focus on High-Resolution X-ray Spectroscopy

Abstract: Neptunium­(V) and uranium­(VI) are precipitated from an aqueous potassium–sodium-containing carbonate-rich solution, and the solid phases are investigated. U/Np M4,5-edge high-energy resolution X-ray absorption near edge structure (HR-XANES) spectroscopy and Np 3d4f resonant inelastic X-ray scattering (3d4f RIXS) are applied in combination with thermodynamic calculations, U/Np L3-edge XANES, and extended X-ray absorption fine structure (EXAFS) studies to analyze the local atomic coordination and oxidation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…4a shows the HERFD data at the U M 4 edge of the UO 2 , UO 3 and KUO 3 , published by Leinders and co-workers 76 as a representative example of the oxidations state detection in tetravalent (UO 2 ), hexavalent (UO 3 ) and pentavalent (KUO 3 ) uranium systems. Similar trends were observed later for the plutonium [61][62][63][64] and neptunium 71 systems in different chemical states.…”
Section: Oxidation State Verificationsupporting
confidence: 86%
See 1 more Smart Citation
“…4a shows the HERFD data at the U M 4 edge of the UO 2 , UO 3 and KUO 3 , published by Leinders and co-workers 76 as a representative example of the oxidations state detection in tetravalent (UO 2 ), hexavalent (UO 3 ) and pentavalent (KUO 3 ) uranium systems. Similar trends were observed later for the plutonium [61][62][63][64] and neptunium 71 systems in different chemical states.…”
Section: Oxidation State Verificationsupporting
confidence: 86%
“…The actinide M 4,5 HERFD-XANES method gives the opportunity to fingerprint the oxidation state of the actinidecontaining materials. The first U M 4 experiment has been done on the mixed uranium oxides 3 , which was followed by several other Please do not adjust margins Please do not adjust margins studies on the chemical state verification in actinide systems 3,6,9,12,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] . Fig.…”
Section: Oxidation State Verificationmentioning
confidence: 99%
“…The possibility of accurately reproducing with DFT calculations the trends correlated to local coordination offers a powerful tool for U M 4,5 HERFD XANES analysis, which can be extended to actinides with empty and singly occupied 5fshells. 10,24 ■ EXPERIMENTAL AND COMPUTATIONAL DETAILS Details on sample preparation and characterization can be found in ref 25 for CaUO 4 , Sr 3 UO 6 , and SrUO 4 and ref 3 for Cs 2 UO 2 Cl 4 . X-ray diffraction (XRD) showed that each compound was single-phase and well crystallized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a recent work, good agreement was obtained neglecting the CH. 24 In other cases, the ground-state f-DOS from DFT did not reproduce the correct separation between A and C, probably because of the absence of the CH effect. 3,23 Figure S1 reports the inclusion of spin orbit and CH in two steps.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51] XANES at the metal L and M edges is also used in Ln and An chemistry research. 26,36,[52][53][54][55][56][57][58][59][60][61][62][63][64][65] The L edge probes dipole-allowed 2p → nd transitions and also provides information about the fshell occupation. The (relative) intensity between the spectral features, and the energy of the main edge, are very sensitive to the metal oxidation state and f-electron count.…”
Section: Introductionmentioning
confidence: 99%